Perancangan Mobile Application Alat Pantau Kualitas Air Kolam Berbasis Internet of Things - Yohanes Anton Nugroho; Muhammad Fitra Pratama (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2020)
Changes in temperature, pH, and turbidity in concrete fish ponds greatly impact to the fish survival. Initial observations showed that among 3.067 fish seeds, 1.633 fish (53%) died and only 1.434 fish (47%) was successfully harvested. The application of water quality monitoring devices from concrete pools designed based on the Internet of Things technology has been tested. The monitoring equipment will not function optimally without an application that functions to receive monitoring data and then take action. Pool water quality monitoring equipment connected to the cloud using a GSM network connection. The recorded data is then displayed on the water quality monitoring application that designed using the Android operating system. Application design is developed using a User-Centered Design approach, where the design process was carried out by considering several variables: ease for use, clarity of information delivery, the fulfillment of needs, and appearance. Based on the results of the design evaluation, weaknesses can be determined, namely, difficulty to find the search menu for click history data, find the refresh button, read the results of searching for historical data, and read data in tables and graphs. Based on this, further improvements can be made to improve the application being made. The monitoring equipment is expected to provide information to pond managers to immediately take action if changing in pH and temperature beyond the limit so that the fish mortality rate can be minimized.